The impact of transformational, transactional, and visionary leadership styles on the quality of education of Madrasah Aliyah - R. Asep Hidayat, Sugiri; Syarifudin, Encep; Fauzi, Anis (Rafandha Press, 2025)
Background: The head of the madrasah has the responsibility to influence all parties involved to work together in achieving the objectives of the madrasah. This study used a quantitative approach. This type of research uses descriptive research to solve or answer problems at hand by collecting data, classification, analysis, conclusions, and reports. Research Objectives Want to know transformational leadership – transactional and visionary madrasah heads have a simultaneous influence on the quality of education at the research site. Method: The population in this study is all teachers and education staff in Madrasah Aliyah Negeri 1 and 2 Serang city, Madrasah Aliyah Negeri 1 Serang Regency and Madrasah Aliyah Negeri 2 Tangerang totaling 200 people. Sampling technique Using the formula from Slovin, the number of samples of this study was obtained as many as 136 people. The data collection technique uses documentation studies and questionnaire techniques. Research Objectives Want to know transformational leadership – transactional and visionary madrasah heads have a simultaneous influence on the quality of education at the research site. Findings: The results showed that there was a significant influence of transformational leadership style, transactional leadership style and visionary leadership style together on the quality of madrasah education in Banten with an adjusted R2 of 72.2% and the remaining 27.8% influenced by other factors not studied in this study.